72.7k views
1 vote
2x+5y=25 3x-y=12 con metodo de sustitución​

User Cechinel
by
5.6k points

1 Answer

1 vote

Answer:

x = 5, y = 3

Explanation:

2x + 5y = 25

3x - 1y = 12

we can multiply the second equation by 5 and then add it to the first equation, which will allow us to solve for 'x'; then we solve for 'y'

5(3x - 1y) = 12(5)

15x - 5y = 60

2x + 5y = 25

+ 15x - 5y = 60

17x = 85

x = 5

plug '5' in for 'x' to solve for 'y':

2(5) + 5y = 25

10 + 5y = 25

5y = 15

y = 3

User Bytrangle
by
4.4k points